The association between nutrition education and knowledge of food high in added sugar, salt, and saturated fat in college students - Hlophe, Nokwanda (My University, 2023)
Background: College students have become more susceptible to increased risks of chronic diseases due to high intakes of problematic nutrients, such as added sugar, salt, and saturated fat, which are detrimental to their health. Moreover, busy student lifestyles and reliance on fast food consumption elevates the risk of prolonged consumption of unhealthy foods. This study’s purpose was to assess the association between nutrition education and knowledge of food high in added sugar, salt, and saturated fat in college students. Methods: This was a randomized controlled trial, from primary data collected through an online Qualtrics survey conducted in the Fall of 2017 at Kansas State University. However, it was used as a cross-sectional secondary data analysis in this study. Recruitment was conducted through emails and word of mouth. The research period was ten weeks, with a randomized control (n-16) and intervention (n-16) group. Demographic characteristics were captured for age, gender, race, year of school, residence, height measured in centimeters, weight measured in kilograms, and body mass index (BMI) for each college student. A Fisher’s exact test with an alpha of 0.05 was used to evaluate the association between nutrition education and knowledge in the control and intervention group in college students. Results: Findings from the analysis of demographic characteristics showed females (77.14%) responded greater than males (22.86%). Based on race, 85.29% of participants were White, 5.88% were Black or African-American, 2.88% were Asian, and others represented 5.88%. Height for men (M= 182.09, SD=6.18) while females (M=1164.14, SD=5.63) were shorter. Weight for male students was 86.25 Kg (SD=19.83) and for females 67.67 Kg (SD=14.37). The intervention group showed a significant difference in knowledge change related to food items under the fat category, such as pasta (p= 0.03725) and cheese (p= 0.0000008551). Salt or sodium, saturated fats, and added sugars had no significant difference in knowledge change. Conclusion: Nutrition education influenced knowledge change about the fat content of plain pasta and cheese and the sodium content of pickles. However, there was no significant difference in knowledge change on added sugar, salt, and saturated fats in the intervention group compared to the control group. More research is needed to assess the impact nutrition education has on change in knowledge of foods high in added sugar, salt, and saturated fat among college students.
Keywords: Healthy eating patterns; added sugar; salt; saturated fat; nutrition education; chronic diseases; college students